2018
DOI: 10.1182/blood-2017-12-820605
|View full text |Cite
|
Sign up to set email alerts
|

High-grade B-cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements with diffuse large B-cell lymphoma morphology

Abstract: High-grade B-cell lymphoma with and and/or rearrangements (HGBL-DH/TH) is a newly defined entity in the latest World Health Organization Classification. Accurate diagnosis would appear to mandate fluorescence in situ hybridization (FISH) for all tumors with diffuse large B-cell lymphoma (DLBCL) morphology. We present the results of FISH, cell-of-origin, and immunohistochemistry (IHC) testing from 1228 DLBCL biopsies from 3 clinical trials and a population-based registry. HGBL-DH/TH made up 7.9% of the DLBCL, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
173
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(190 citation statements)
references
References 21 publications
4
173
1
5
Order By: Relevance
“…[2][3][4] The inclusion of DLBCL DE/TE for additional molecular assessment is clearly substantiated by recent reports on DLBCL DH cases within the DLBCL DE/TE group. 3,4,15,16 Most of the morphological and immunohistochemical characteristics identified in the group were consistent with those presented in previous reports; however, 2 were found to be intriguingly different. Firstly, almost 70% of the HGBL/DLBCL group displayed an ABC subtype phenotype when we assessed the COO using the Hans algorithm.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[2][3][4] The inclusion of DLBCL DE/TE for additional molecular assessment is clearly substantiated by recent reports on DLBCL DH cases within the DLBCL DE/TE group. 3,4,15,16 Most of the morphological and immunohistochemical characteristics identified in the group were consistent with those presented in previous reports; however, 2 were found to be intriguingly different. Firstly, almost 70% of the HGBL/DLBCL group displayed an ABC subtype phenotype when we assessed the COO using the Hans algorithm.…”
Section: Discussionsupporting
confidence: 90%
“…3,5,17,18 However, it must be emphasized that trials of more intensive or novel regimens in HGBL have reported inconsistent results, and the evidence is still not strong enough to prepare distinct treatment guidelines for HGBL patients. 2,3,15,[19][20][21][22][23] This further emphasizes the need for better distinction of HGBL as a highly heterogeneous, provisional category of lymphomas, which should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the NCCN guidelines recommend a more focused approach based upon biological predictors, suggesting patients with a GCB‐like immunophenotype and the expression of MYC and BCL2 or BCL6 by immunohistochemistry should undergo FISH detection . This is based on the observation that the majority of DHL will be of the GCB‐like pheonotype . This strategy would however miss approximately one quarter of tumours with DHL or THL with BCL2 rearrangements and one‐third of all HGBL‐DH/TH.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that roughly 10% of HGDH have a lower expression of MYC. In such cases, FISH should be recommended 11 .…”
mentioning
confidence: 99%